Relationship between the degree of certainty of the registration of the trade name and its level of enforceability in the cases resolved by Indecopi, Peru, 2011-2013 - Sologuren Alvarez, Juan Enrique (2016)
Objective: The objective of this investigation ¡is to establish the relationship between the degree of certainty of the date of first use of the commercial name that provides the registration of distinctive signs and the level of effectiveness of ownership when registered. This investigation is of national scope, as it includes the cases of application, opposition and nullity of registration of commercial names resolved by the Competition and Intellectual Property Defense Court of INDECOPI between 2011 and 2013. Methodology: The methods used were analysis and synthesis of national and foreign doctrine, the exegetical and dogmatic method, comparative legal method and descriptive statistical analysis. Results: The results show that the simple use of the trade name does not prevent other confusable distinctive signs from being used or have the possibility to register, which forces its owner to file opposition or registration nullities; And that the registration of commercial names, which recognizes the date of their first use, is only granted after verifying the absence ofrisk of confusion with other preexisting distinctive signs and their knowledge in all or most of the country, determining that in the event of a dispute Only the current use of the sign. Conclusion: Our investigation allows us to conclude that the Register of distinctive signs providesfull certainty of the date ofthe first use of the trade name and that when it is registered obtains a greater level of third-party effectiveness, being proved its direct and significant relationship